Mountain Tourism and Climate Change: Implications for the Nepal Himalaya - Nepal, Sanjay K (Nepal Tourism and Development Review, 2013)
Despite the global nature of tourism industry and its economic contributions, scholars of climate change research have hardly acknowledged the threat of climate change to the tourism industry. Tourism scholars have rectified this situation to a certain extent by demonstrating how the industry has become vulnerable to climate change and drawing attention to the need for adaptation and mitigation strategies specific to this sector. This paper provides an overview of climate change challenges in tourism destinations in the mountains, with a particular emphasis in developing countries and with specific reference to the Nepal Himalaya. It outlines several adaptation strategies at the local, state and national levels. Climatic effects on high mountains are very specific; climate change is likely to trigger the rates and intensity of natural hazards such as landslides, avalanches and flooding with dramatic consequences for tourism destinations. Adaptation strategies in the context of natural hazards must consider the level of risks and weigh it against costs and benefits of adaptation. If benefits outweigh the costs, it is likely that the level of local responses to adaptation will be high. If the level of risk and associated costs is too high, local communities may be fatalistic in their attitude to climate change impacts. The paper outlines adaptation strategies for tourism stakeholders, resident communities and governments and emphasizes that climate change strategies in the tourism sector must be considered as a collaborative effort, with considerations for institutional development, diversification of opportunities, equity and sustainable economic growth. DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7367 Nepal Tourism and Development Review Vol.1(1) 2011 1-14